Secondary thoracic goiter - Delgado, Bolívar; Chifflet, Juan; Lista, Ricardo (Cirugía del Uruguay, 1996)
The authors, based on a series of 20 patients they had operated for secondary thoracic goíter, revise a series of issues on the therapy of these cases: surgical indication, intraoperative management of the air way and postoperative immediate complications. They point out: surgical indication as a first choice because of the risk for acute respiratory complications, elective cervical access, few problems in the intraoperative management of the air way and the practica/ inexistence of tracheomalacia as postoperative management problem.